THE USE OF ARTIFICIAL INTELLIGENCE AS A VIRTUAL PEDAGOGICAL ASSISTANT TO STRENGTHEN EXECUTIVE SKILLS IN THE EDUCATIONAL ENVIRONMENT - Angela Julieth Puerto Vargas; Nidia Janeth Ruiz Mendoza (LÍNEA IMAGINARIA, 2025)
The essay discusses the use of artificial intelligence as a virtual pedagogical assistant to enhance educational capabilities in the educational environment. It reveals that there are different types of artificial intelligence and that their use has different purposes. Artificial intelligence operates with mathematical models that allow for anticipating future events or circumstances. It helps humans rethink ideas and guide pedagogical actions for teachers and students. It also helps in the development of cognitive skills, enabling reasoning and response in critical situations. The essay highlights that artificial intelligence can be a valuable ally for managerial and high-ranking positions within educational institutions. Implementing artificial intelligence, particularly virtual teaching assistants, can significantly enhance executive skills in the educational field.